Characterization of the splicing function of pseudouridine Ψ5 in U1 small nuclear RNA - Yong, Jing Yen (2018)
Pseudouridine (Ψ) is the major post-transcriptionally modified nucleotide in RNA. The 5’ end of U1 snRNA contains two evolutionarily conserved pseudouridines, Ψ5 and Ψ6, yet, their role in recognition of thousands of 5’ss variants remains to be established. Therefore, in our study, we investigated the role of Ψ5 of U1 snRNA in splicing by utilizing CRISPR-Cas9 genome editing tool to knock out ACA47, the small cajal RNA that guides Ψ5 modification, in HEK293T cells. All HEK293T results were then cross-validated with K562 cells, and we expected that both cell types would produce similar splicing changes upon ACA47 knockout. With even partial ACA47 knockout of HEK293T obtained, we showed for the first time that Ψ5 of U1 snRNA plays considerable regulatory role in splicing. Surprisingly, HEK293T partial knockout and K562 knockout showed cell line-specialized alternative splicing changes. Our findings are useful not only for mechanistic understanding of mammalian 5’ss recognition, more importantly, they might be helpful in disease diagnosis with mutations at 5’ss.